Comparison of serum uric acid, bilirubin, and C-reactive protein as prognostic biomarkers of in-hospital MACE between women and men with ST-segment elevation myocardial infarction - Baumann, Stefan; Huseynov, Aydin; Köpp, Johanna; Jabbour, Claude; Behnes, Michael; Becher, Tobias; Lang, Siegfried; Borggrefe, Martin; Lehmann, Ralf; Akın, Ibrahim (Angiology, 2016)
Levels of C-reactive protein (CRP), uric acid (UA), and total bilirubin (TB) are associated with coronary artery disease and major adverse cardiac events (MACEs) in patients with ST-segment elevation myocardial infarction (STEMI). We retrospectively included 1167 patients with STEMI who underwent percutaneous coronary intervention and routine blood sampling. The study cohort consisted of 803 patients (73.1% male, mean age 62.5 ± 13.4 years). In men, the levels of CRP, TB, and UA were significantly higher in the MACE than in the non-MACE group (P < .05). The receiver-operating characteristic (ROC) analysis shows that CRP (area under the curve [AUC]: 0.59; 95% confidence interval [CI]: 0.53-0.66; P = .014) and TB (AUC: 0.58; 95% CI: 0.51-0.65; P = .019) are significantly associated with MACE but not UA (AUC: 0.61; 95% CI: 0.42-0.76; P = .083). Logistic regression revealed CRP (odds ratio [OR] 1.01; 95% CI: 1.00-1.01; P = .006) and TB (OR 2.03; 95% CI: 1.12-3.40; P = .007) as an independent predictor for MACE. In women, none of the biomarkers was associated with MACE by ROC analysis or logistic regression analysis. This study demonstrated that high CRP and TB serum levels have a prognostic association with in-hospital MACE in male patients with STEMI.